2021
DOI: 10.21037/apm-21-1001
|View full text |Cite
|
Sign up to set email alerts
|

Levels and clinical significance of serum homocysteine (Hcy), high-density lipoprotein cholesterol (HDL-C), vaspin, and visfatin in elderly patients with different types of coronary heart disease

Abstract: Background: To investigate the levels and clinical significance of serum homocysteine (Hcy), high-density lipoprotein cholesterol (HDL-C), visceral adipose tissue-derived serine protease inhibitor (vaspin), and visceral fat-specific adipokine (visfatin) in elderly patients with different types of coronary heart disease (CHD).Methods: A total of 208 elderly patients with CHD admitted to our hospital were selected as the observation group, and 57 healthy volunteers who received physical examinations during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The visualizations completed for the top four covariates were concordant with current literature around the relationship between these covariates and coronary artery disease: there is strong epidemiological and physiological evidence for the link between increased age and cholesterol as major risk factors for coronary artery disease [26][27][28]. The non-linear relationship between cholesterol and coronary artery disease matches survival-modeling and restricted PLOS ONE cubic spline analysis from other studies [28][29][30][31][32][33][34][35][36]. Furthermore, multiple genetic and sociological studies have found that family history is a significant risk factor for coronary artery disease [37][38][39][40].…”
Section: Plos Onesupporting
confidence: 74%
“…The visualizations completed for the top four covariates were concordant with current literature around the relationship between these covariates and coronary artery disease: there is strong epidemiological and physiological evidence for the link between increased age and cholesterol as major risk factors for coronary artery disease [26][27][28]. The non-linear relationship between cholesterol and coronary artery disease matches survival-modeling and restricted PLOS ONE cubic spline analysis from other studies [28][29][30][31][32][33][34][35][36]. Furthermore, multiple genetic and sociological studies have found that family history is a significant risk factor for coronary artery disease [37][38][39][40].…”
Section: Plos Onesupporting
confidence: 74%
“…Recent studies have shown that elevated Hcy can promote lipid deposition in foam cells and accelerate the progression of atherosclerosis [ 46 ]. Clinical studies have found that the plasma expression of Hcy is elevated in CHD [ 47 , 48 ] and is related to coronary artery stenosis degree [ 49 ]. Therefore, Hcy can predict major adverse cardiovascular events and has important clinical significance in determining the condition and prognosis of CHD patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Risk of CAD is monitored by lipid profile estimation especially the LDL and non-HDL-C levels. In a multi ethnic study conducted in patients (aged 52.3±17.9 years) with atherosclerotic cardiovascular disease, LDL levels were found to be higher than normal (9). The Copenhagen general population study conducted in 13,015 statin-treated patients found higher levels of apo B and Non-HDL-C were associated with the increased risk of all-cause mortality and myocardial infarction (6).…”
Section: Resultsmentioning
confidence: 98%